Biochemical Characterization of VIM-39, a VIM-1-Like Metallo-β-Lactamase Variant from a Multidrug-Resistant Klebsiella pneumoniae Isolate from Greece - Papagiannitsis, Costas C. (Antimicrob Agents Chemother, 2015)
VIM-39, a VIM-1-like metallo-β-lactamase variant (VIM-1 Thr33Ala His224Leu) was identified in a clinical isolate of Klebsiella pneumoniae belonging to sequence type 147. VIM-39 hydrolyzed ampicillin, cephalothin, and imipenem more efficiently than did VIM-1 and VIM-26 (a VIM-1 variant with the His224Leu substitution) because of higher turnover rates.